THE USE OF ARTIFICIAL INTELLIGENCE AS A PERSONAL TUTOR IN EDUCATION: A LITERATURE REVIEW ON PERSONALISATION AND ADAPTATION OF LEARNING MATERIALS BASED ON STUDENT DATA ANALYSIS - Rizki Fauzi; Al-Amin (CV. ADIBA AISHA AMIRA, 2025)
The development of artificial intelligence (AI) technology has brought significant changes to the education sector, particularly in efforts to create more personalised and adaptive learning systems. This study aims to examine the use of AI as a personal tutor in education through a literature review approach that focuses on two main aspects, namely personalisation and adaptation of learning materials based on student data analysis. Using a literature review method from various reliable academic sources, this study analyses the role of AI in understanding student learning behaviour, adjusting learning content, and providing data-based automatic feedback. The results of the study show that the application of AI tutors can improve the effectiveness, efficiency, and relevance of the learning process while expanding access to quality education. However, issues of data ethics and privacy, algorithmic bias, and digital infrastructure readiness are important challenges that need to be addressed. This study emphasises that the integration of AI in education must be oriented towards human-machine collaboration by balancing technological, pedagogical, and ethical aspects in order to create a sustainable and humanistic learning experience.